Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pt Budi Sehat Di Surakarta - Setiawan Sutowo Putro, Bagus; , Jati Waskito, SE., M.Si (2017)
This research aimed to analyze the influence of the workload on the employees' performance of PT. Budi Sehat in Surakarta, to analyze the influence of the work stress on the employees' performance of PT. Budi Sehat in Surakarta and to analyze the influences of the workload and the work stress on the employees' performance of PT. Budi Sehat in Surakarta. The data used in this research were the primary data obtained from the result of distributing questionnaire about the work stress, the over workload, the work situation, the employees' performance. The method of data collection in this research was through the primary data collection and documentation. The Method of data analysis used in this research was the research instrumental research using the validitytest, reliability test, classical assumption test, and hypothetical test. The results of this research revealed that: 1) There is a negatively significant influence of the workload on the employees' performance of PT. Budi Sehat in Surakarta which is proved by the the p-value 0.005, 2) There was a negatively significant influence of the work stress on the employees' performance of PT. Budi Sehat in Surakarta which is proved by the p-value 0.032 and 3) There is a simultant influence of the workload on the employees' performance of PT. Budi Sehat in Surakarta which is proved by the result of Fcount as much as 11.745 and the significance value (p-value) as much as 0.000.